Structural failure : technical, legal and insurance aspects : proceedings of the founding symposium of the International Society for Technology, Law and Insurance, 18-19 November 1993, Vienna, Austria /: technical, legal and insurance aspects : proceedings of the founding symposium of the International Society for Technology, Law and Insurance, 18-19 November 1993, Vienna, Austria. (2014) - Unknown
No abstract available